IMPROVING STUDENTS’ MASTERY OF SIMPLE PAST TENSE USING GRAMMARLY - Alia Febrian; ⁠Eusabinus Bunau; Eni Rosnija (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This classroom action research aims to improve students' mastery of the simple past tense in Grade X at SMA Taruna Bumi Khatulistiwa through the use of Grammarly in the learning process. The research was conducted in two cycles, each consisting of planning, action, observation, and reflection stages, involving 27 Grade X-C students. Data were collected through observation sheets, field notes, student assignments, and portfolios. The results of the research showed a gradual improvement in pupils' command of simple past tense sentences, particularly in the use of verb 2 in positive sentences, verb 1 in negative and interrogative sentences, and the addition of appropriate time adverbs. Grammarly provided immediate feedback that assisted the learners in identifying and correcting the grammatical errors independently. The research results indicate that Grammarly is an interesting tool for improving mastery of the simple past tense.